(untitled) (Research, Society and Development, 2022)
The present study seeks to correlate the use of face mask and electronic devices in the COVID-19 era with the emergence or worsening of dry eye disease. Online databases were used to identify articles published in 2020 and 2021, using the descriptors “dry eye syndromes”, “covid-19”, “diagnosis” and “asthenopia” found in MeSH (Medical Subject Headings), associated with the Boolean operator AND. After reading the titles, abstracts and texts in full, seventeen articles were selected to compose the work. In addition, at the recommendation of an expert, the world’s largest study on dry eye disease, TFOS DEWS II, published in the Ocular Surface Journal in July 2017, was also added to this review. The average duration of use of electronic devices has been found to triple in the COVID era, and just two continuous hours develop digital eye fatigue, as diminished and incomplete blinking leads to ocular surface compromise and asthenopic symptoms. In addition, inadequate mask seals dissipate air around the eyes, causing rapid tear film evaporation and corneal exposure. In view of the studies, it can be concluded that the correlation between the factors presented and dry eye disease really exists. In addition, the ocular manifestation proved to be heterogeneous and affects not only aspects of physical health but also emotional health and negatively impacts the patient’s quality of life.